Pengaruh Pemberian Teknik Range Of Motion (Rom) Terhadap Kekuatan Otot Pada Pasien Stroke Non Hemoragic (Snh) - Herlina; Fajar Yudha; Septi Kurniasari; Yoga Nicolas Pradipta (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction Stroke sufferers can recover completely if treated within the first 6 hours (the golden period), but if it is too late, long-lasting disability or physical weakness can occur. To reduce the sequelae of stroke, in addition to being done with physiotherapy, ROM (Range of Motion) exercises can be done. The ROM technique is a series of simple exercises to increase muscle strength. The purpose of this study was to determine the effect of giving the ROM technique on the muscle strength of stroke patients. Quasi-experimental research design pre and post test design with a total sample of 26 people and purposive sampling technique. Data were collected using observation sheets and univariate and bivariate data analysis. The results showed that before the ROM intervention most of the SNH patients with "Slightly Bad" (score 2) and "Medium" (score 3) each were 12 people (50%), after the ROM intervention the muscle strength mostly became "Good". ” (score 4) as many as 15 people (62.5%). The results of the Paired t-Test statistical analysis obtained a value of p = 0.000 (p 0.05), meaning that there was an effect of giving the ROM technique on muscle strength in SNH patients in the Flamboyant Room of Mardi Waluyo Hospital, Metro Lampung.